Towards Core Competencies for Health Policy and Systems Research (HPSR) Training: Results From a Global Mapping and Consensus-Building Process - Meike J. Schleiff; Avanti Rangnekar; Francisco Oviedo Gomez; Gina Teddy; David H. Peters; Dina Balabanova (Kerman University of Medical Sciences, 2022)
BackgroundAs the field of health policy and systems research (HPSR) continues to grow, there is a recognition of the need for training in HPSR. This aspiration has translated into a multitude of teaching programmes of variable scope and quality, reflecting a lack of consensus on the skills and practices required for rigorous HPSR. The purpose of this paper is to identify an agreed set of core competencies for HPSR researchers, building on the previous work by the Health Systems Global (HSG) Thematic Working Group on Teaching & Learning. MethodsOur methods involved an iterative approach of four phases including a literature review, key informant interviews and group discussions with HPSR educators, and webinars with pre-post surveys capturing views among the global HPSR community. The phased discussions and consensus-building contributed to the evolution of the HPSR competency domains and competencies framework. ResultsEmerging domains included understanding health systems complexity, assessing policies and programs, appraising data and evidence, ethical reasoning and practice, leading and mentoring, building partnerships, and translating and utilizing knowledge and HPSR evidence. The development of competencies and their application were often seen as a continuous process spanning evidence generation, partnering, communicating and helping to identify new critical health systems questions. ConclusionThe HPSR competency set can be seen as a useful reference point in the teaching and practice of high-quality HPSR and can be adapted based on national priorities, the particularities of local contexts, and the needs of stakeholders (HPSR researchers and educators), as well as practitioners and policy-makers. Further research is needed in using the core competency set to design national training programmes, develop locally relevant benchmarks and assessment methods, ad evaluate their use in different settings.